The Impact of personality characteristics on the “similar to me" effect: A research in Mazandaran Province Hospitals - Abbas Narhesiyan; Jabbar Babashahi; Mansour Ranjbar (پژوهش‌های روانشناختی در مدیریت, 2015)
As managers are obliged to make various and diverse decisions, we can expect that these decisions are influenced by various variables and the managers deviate in decision making. One of the factors that affects manager’s perceptions during decision making process is “similar to me” factor. In this paper, we try to explain influential personality characteristics (such as narcissism, internal locus control and external locus control) on occurrence of “similar to me” effect. Research findings show that there is a meaningful positive relationship between “similar to me” effect and personality characteristic (narcissism and internal locus control) and meaningful negative relationship between “similar to me” effect and external locus control. Statistical population includes managers that work in hospitals of Mazandaran province.